„Nescit quo flectere puppem" (Corippi Johan. I 273). Hipoteza kontaminacyjna - Jakielaszek, Jarosław (Vox Patrum, 2005)
The paper examines a Late Latin construction consisting of a relative or an interrogative pronoun followed by a bare infinitive. It has been often proposed that the syntactic structure of such sentences results from a contamination of two distinct clause types. This paper proposes an analysis in terms of the Minimalist framework, rejecting the traditional approach and explaining syntactic and semantic properties of the structure on the basis of mechanisms independently motivated for other Latin structures. The surface shape of such clauses is argued to result from changes in morphological parameters. The analysis provides therefore support for the thesis that language change involves primarily the morphological module, which remains the main locus of diachronic and synchronic variation.